2017
DOI: 10.1007/s12035-016-0254-z
|View full text |Cite
|
Sign up to set email alerts
|

A Small Organic Compound Mimicking the L1 Cell Adhesion Molecule Promotes Functional Recovery after Spinal Cord Injury in Zebrafish

Abstract: Tacrine is a small organic compound that was discovered to mimic the functions of the neural cell adhesion molecule L1 by promoting the cognate functions of L1 in vitro, such as neuronal survival, neuronal migration, neurite outgrowth, and myelination. Based on studies indicating that L1 enhances functional recovery in different central and peripheral nervous system disease paradigms of rodents, it deemed interesting to investigate the beneficial role of tacrine in the attractive zebrafish animal model, by eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 72 publications
2
19
0
Order By: Relevance
“…We generally translated a protocol using Zeiss confocal microscope for laser injury 31,32 and a method based on Olympus FV1000 MPE two-photon laser scanning microscope 33 to Leica TCS SP5 LSM equipped with two-photon laser, but with minor alterations. In brief, the embedded embryos were observed under a 20x water lens and the selected axons were placed in the center of the field of vision.…”
Section: Methodsmentioning
confidence: 99%
“…We generally translated a protocol using Zeiss confocal microscope for laser injury 31,32 and a method based on Olympus FV1000 MPE two-photon laser scanning microscope 33 to Leica TCS SP5 LSM equipped with two-photon laser, but with minor alterations. In brief, the embedded embryos were observed under a 20x water lens and the selected axons were placed in the center of the field of vision.…”
Section: Methodsmentioning
confidence: 99%
“…Intriguingly, these chemical compounds trigger specifically L1-mediated or PSA-mediated cell signaling in vitro and in vivo. Follow-up studies confirmed that different L1 and PSA mimetics improve functional recovery after spinal cord and femoral nerve injury in mice and zebrafish [20, 2225]. …”
Section: Introductionmentioning
confidence: 99%
“…Sequences for MOs targeting Chst-11 and a standard control MO have been described and were tested for efficacy (25,27). To validate the efficacy of the Chst-14 MOs, a fragment of the cDNA from Chst-14 mRNA (NM_212829) from 71 to 482 bp of the coding sequence (containing the Chst-14 MO target sequence) was inserted into the BamHI and EcoRI sites of pCS2-Myc to construct the plasmid pCS2-Chst-14-c-Myc (Guangzhou DianLi Biotechnology Co., Guangzhou, China).…”
Section: Mo Construction and Validationmentioning
confidence: 99%
“…The head, yolk sac, and tail of the 4 and 6 dpf larvae were removed under a stereoscope (JW-101; OKA; Wuzhou, China), and spinal cords were isolated and total protein was extracted by homogenizing the tissues in RIPA buffer. After centrifugation (10,000 g, 4°C, 10 min), the supernatants were boiled for 10 min in 1% SDS, and Western blot analysis was performed as previously described (27). The following antibodies were used for Western blot analysis: anti-c-Myc (1:200, sc-40; Santa Cruz Biotechnology, Dallas, TX, USA), anti-b-actin antibody (1:1000, sc-47778; Santa Cruz Biotechnology), and horseradish peroxidase-conjugated secondary antibody (1:1000, goat anti-mouse BA1051; Boster Biologic Technology, Wuhan, China).…”
Section: Mo Construction and Validationmentioning
confidence: 99%
See 1 more Smart Citation